Corporate Governance In Institutions Offering Islamic Financial Services : Issues And Options - Grais, Wafik (The World Bank, 2006)
This paper reviews institutions offering Islamic financial services (IIFS) corporate governance challenges and suggests options to address them. It first points out the importance of corporate governance for IIFS, where it would require a distinct treatment from conventional corporate governance and highlights three cases of distress of IIFS. It then dwells on prevailing corporate governance arrangements addressing IIFS' needs to ensure the consistency of their operations with Islamic finance principles and the protection of the financial interests of a stakeholders' category, namely depositors holding unrestricted investment accounts. It raises the issues of independence, confidentiality, competence, consistency, and disclosure that may bear on pronouncements of consistency with Islamic finance principles. It also discusses the agency problem of depositors holding unrestricted investment accounts. The paper argues for a governance framework that combines internal and external arrangements and relies significantly on transparency and disclosure of market relevant information